Synchrotron self-absorption in GRB afterglows: the effects of a thermal electron population. Issue 3 (16th August 2018) - Warren, Donald C; Barkov, Maxim V; Ito, Hirotaka; Nagataki, Shigehiro; Laskar, Tanmoy
ABSTRACT: In the standard synchrotron afterglow model, a power law of electrons is responsible for all aspects of photon production and absorption. Recent numerical work has shown that the vast majority of particles in the downstream medium are actually 'thermal' particles, which were shock heated but did not enter the Fermi acceleration process (the name stands in contrast to the non-thermal high-energy tail, rather than connoting a Maxwellian distribution). There are substantial differences at optical and higher energies when these thermal electrons participate in the afterglow, but early work along these lines ignored the radio end of the electromagnetic spectrum. We report here on an extension of previous Monte Carlo simulations of gamma-ray burst afterglows. The model now includes the synchrotron self-absorption (SSA) process and so can simulate afterglows across the entire EM spectrum, and several orders of magnitude in time. In keeping with earlier work, inclusion of the thermal electrons increases the SSA frequency by a factor of 30, and the radio intensity by a factor of 100. Furthermore, these changes happen with no modification to the late optical or X-ray afterglow. Our results provide very strong evidence that thermal electrons must be considered in any multiwavelength model for afterglows.